2010
DOI: 10.1111/j.1365-2141.2010.08342.x
|View full text |Cite
|
Sign up to set email alerts
|

The class‐I HDAC inhibitor MGCD0103 induces apoptosis in Hodgkin lymphoma cell lines and synergizes with proteasome inhibitors by an HDAC6‐independent mechanism

Abstract: Summary Inhibition of histone deacetylase 6 (HDAC6)-dependent aggresome function by pan HDAC inhibitors was recently reported to be a key mechanism underlying the synergistic activity between proteasome inhibitors and HDAC inhibitors in a variety of tumour types. Because these combinations induce significant thrombocytopenia in vivo, we examined whether less toxic, isotype-selective HDAC inhibitors may still synergize with proteasome inhibitors, and if so, by what mechanisms. Here, we showed that the class I H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…In contrast, the pan-HDI TSA (46,47) (46,47,49,50). In contrast to TSA and apicidin, MS-275 did not inhibit SOST expression, but showed a bell-shaped about 2-fold stimulation with a maximum at 1 M. A similar response was obtained with MGCD0103 (51,52), another potent HDAC1 inhibitor (data not shown). As the class I HDAC8 is not expressed in UMR106 cells (Fig.…”
Section: Pth Stimulates Nuclear Localization Of Hdac5 In Umr106 Cellssupporting
confidence: 61%
“…In contrast, the pan-HDI TSA (46,47) (46,47,49,50). In contrast to TSA and apicidin, MS-275 did not inhibit SOST expression, but showed a bell-shaped about 2-fold stimulation with a maximum at 1 M. A similar response was obtained with MGCD0103 (51,52), another potent HDAC1 inhibitor (data not shown). As the class I HDAC8 is not expressed in UMR106 cells (Fig.…”
Section: Pth Stimulates Nuclear Localization Of Hdac5 In Umr106 Cellssupporting
confidence: 61%
“…We demonstrated that panobinostat is among the most active HDAC inhibitors against HL cell lines in vitro, with IC 50 in the nanomolar ranges. 20 The antiproliferative activity involved regulation of several oncogenic pathways, including caspase activation and induction of apoptosis, inhibition of the activation of STAT5 and STAT6, and inhibition of tumor angiogenesis and regulation of glucose uptake. Our data also provide a mechanistic rationale for combining panobinostat with everolimus for the treatment of patients with HL.…”
mentioning
confidence: 99%
“…Previous studies indicate that MGCD10103 increases caspase-dependent apoptosis while inhibiting autophagy through the activation of the PI3K/AKT/mTOR pathway [81,82]. Furthermore, MGD10103 increased NF-κB activation and resulted in increased TNF-α expression and production [80]. For these reasons, MGCD0103 may not be optimal for treatment for autoimmune diseases, including SLE and RA, which are characterized by increased PI3K/AKT/mTOR signaling and NF-κB activation [83][84][85].…”
Section: Selective Class I Inhibitorsmentioning
confidence: 92%
“…MGCD0103 has been demonstrated to have antiproliferative activity in Hodgkin lymphoma cell lines and B-cell chronic lymphocytic leukemia [79][80][81]. Previous studies indicate that MGCD10103 increases caspase-dependent apoptosis while inhibiting autophagy through the activation of the PI3K/AKT/mTOR pathway [81,82].…”
Section: Selective Class I Inhibitorsmentioning
confidence: 99%